Lyhdyn nään syttyvän ; Rakkaus on sininen - Sorsakoski, Topi, 1952-2011; Hietanen, Pedro, 1949-2023; Agents; Topi Sorsakoski & Agents; EMI Finland ([Helsinki] : EMI Finland, 1989)
2 kappaletta.
Pedro Hietanen (tuottaja).
Topi Sorsakoski & Agents (yhtye). Solisti: Topi Sorsakoski (lauluääni).
[Äänite]
Keywords: Sorsakoski, Topi, -- 1952-2011. -- singlet; iskelmät